2013
DOI: 10.2215/cjn.10641012
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Prevalence of Microalbuminuria 10 Years Later

Abstract: SummaryBackground and objectives A recent meta-analysis found that about 30% of women with a previous preeclamptic pregnancy had persistent microalbuminuria at follow-up. The analysis was, however, based on small studies, and more data are needed.Design, setting, participants, & measurements Using data from the Medical Birth Registry in Norway, this study identified women with or without preeclampsia in their first pregnancy 9-11 years previously (1998)(1999)(2000). Women with diabetes, rheumatic disease, esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 37 publications
(39 reference statements)
1
35
1
1
Order By: Relevance
“…These figures were similar to those seen by whose median ages were 27 years for microalbuminuria group and 28 years for non-microalbuminuria group [26]. On the other hand, our study population were much younger than those seen by Sandvik et al whose patients' mean age was 37.9 years among cases with preeclampsia and 39 years among cases without preeclampsia [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These figures were similar to those seen by whose median ages were 27 years for microalbuminuria group and 28 years for non-microalbuminuria group [26]. On the other hand, our study population were much younger than those seen by Sandvik et al whose patients' mean age was 37.9 years among cases with preeclampsia and 39 years among cases without preeclampsia [27].…”
Section: Discussionsupporting
confidence: 89%
“…The mean blood pressure at booking was 118.5/75 mm Hg for high risk group and 117/75.2 mm Hg for low risk group. Sandvik et al found a slight and non-significant difference between cases with preeclampsia and those with non-preeclampsia [27]. Blood pressure rose at delivery by around 6-9 mm Hg to be 127.2/80.8 mm Hg for high risk group and 124.2/81.2 mm Hg for low risk group.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a recent large Norwegian study (22), PE was not associated with microalbuminuria. In line with the results from Sandvik et al (22), a morning urine sample collected after completion of our study did not show a difference in albuminuria between the groups; all women had albuminuria values within the normal range.…”
Section: Discussionmentioning
confidence: 76%
“…6 The study by Mangos et al 7 reported no differences in eGFR after preeclampsia, but Spaan et al 8 found a lower renal function shortly after preeclampsia and at middle age. In contrast, a study at 10 years postpartum by Sandvik et al 9 shows a high-normal eGFR in former preterm preeclamptic women. In addition, we recently reported a slightly higher renal filtration fraction 10 years postpartum by radioactive tracer measurement in a well-controlled small cohort after early-onset PE.…”
mentioning
confidence: 84%
“…However, some studies that were not included in the meta-analysis report the incidence of proteinuria in fPE being low and similar to that of fHP women. 7,9,11 The conflicting results of the different studies on renal function and albuminuria after preeclampsia might be because of small-sized studies and heterogeneity within the fPE group, including a case-mix of early and late preeclampsia. We, therefore, aimed to study renal function in a large cohort at 10 years postpartum of well-characterized former early-onset PE women.…”
Section: Hypertensionmentioning
confidence: 99%